Presentation - Mansilla, Ricardo (INTER DISCIPLINA, 2021)
This issue of the journal INTER DISCIPLINA dedicates its dossier to obesity. The six articles that compose it provide different approaches to this problem with a wide spectrum of points of view that include food–health relationships, gender perspectives of the problem, testimonies of migrants, the aspects of mental health linked to obesity, and a historical outlook at the phenomenon in the last two decades.